The oximes HI-6 and MMB-4 fail to reactivate soman-inhibited human and guinea pig AChE: A kinetic in vitro study. (1st September 2018) - Worek, Franz; Thiermann, Horst; Wille, Timo
Highlights: We determined the in vitro kinetic interactions of human and guinea pig AChE, soman, HI-6 and MMB-4. In a static assay, HI-6 retarded the inhibition of human AChE by soman. Both oximes were not able to prevent complete inhibition of AChE by soman in a dynamic model. HI-6 and MMB-4 could not reactivate soman-inhibited AChE in a simulated in vivo situation. Abstract: Acetylcholinesterase (AChE) inhibited by the organophosphorus nerve (OP) agent soman underlies a spontaneous and extremely rapid dealkylation ("aging") reaction which prevents reactivation by oximes. However, in vivo studies in various, soman poisoned animal species showed a therapeutic effect of oximes, with the exact mechanism of this effect remaining still unclear. In order to get more insight and a basis for the extrapolation of animal data to humans, we applied a dynamic in vitro model with continuous online determination of AChE activity. This model allows to simulate the in vivo toxico- and pharmacokinetics between human and guinea pig AChE with soman and the oximes HI-6 and MMB-4 in order to unravel the species dependent kinetic interactions. It turned out that only HI-6 was able to slow down the ongoing inhibition of human AChE by soman without preventing final complete inhibition of the enzyme. Continuous perfusion of AChE with soman and simultaneous or delayed (8, 15 or 40 min) oxime perfusion did not result in a relevant reactivation of AChE (less than 2%). In conclusion, the results of the present study indicate a negligible reactivation of soman-inhibited AChE by oximes at conditions simulating the in vivo poisoning by soman. The observed therapeutic effect of oximes in soman poisoned animals in vivo must be attributed to alternative mechanisms which may not be relevant in humans.